Application of Health Assessment Index for assessing the ecological health of River Mahanadi - Bhowmick, Sanjay; M, Sajina A; Samanta, Srikanta; Paul, Samir Kumar; Sudheesan, Deepa; Nag, Subir Kumar; Kumar, Vikash; Baitha, Raju (Journal of the Inland Fisheries Society of India, 2021)
Biotic communities are sensitive to environmental factors and offer an integral perspective of the environmental conditions of a given habitat. Fish are widely used as sentinel species to assess environmental health and are excellent indicators of overall health of rivers. A study was carried out to evaluate and compare the environmental quality of different stretches of River Mahanadi by analyzing fish health using Health Assessment Index (HAI). The HAI values of individual fishes varied from 0 to 200. The fish which got the highest score for HAI was from the winter sample of Sonepur. The lowest score for HAI was recorded at Tikarpara, a site which falls under protected Satkosia river sanctuary. The most common groups of parasites recorded were myxozoans, trichodinids, copepods and monogenetic trematodes. Parasite numbers recorded from Cirrhinus reba supported the HAI hypothesis that higher endoparasite and lower ectoparasite numbers occur at highly impacted areas. The present study suggests that HAI can be used as an effective biological monitoring tool for Indian rivers. Key words Ecological health, Biomonitoring, Parasite